2008
DOI: 10.1088/0029-5515/48/5/054015
|View full text |Cite
|
Sign up to set email alerts
|

Advanced launcher design options for electron cyclotron current drive on ITER based on remote steering

Abstract: Abstract. Electron Cyclotron Current Drive (ECCD) will become the main scheme on ITER for the stabilization of neoclassical tearing modes (NTM) and the control of sawtooth oscillations. The effectiveness of this scheme forms the basis for the requirements of the ITER Upper Port Launcher (UPL). These requirements include the need for steering the mm-wave beam to the pertinent magnetic flux surfaces where the instability develops. Several concepts have been explored; Front Steering where a system of movable mirr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In the early development stage of the launcher, it was found that a design based on remote steering [4], although attractive because movable parts would have been placed in a secondary vacuum away from the plasma, was unable to deliver sufficiently focused beams over the whole steering range. The adoption of a front steering concept [5] has allowed a larger flexibility in the design of the beams, which in turn has led to an optimization of the distribution of the tasks between EL and UL [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the early development stage of the launcher, it was found that a design based on remote steering [4], although attractive because movable parts would have been placed in a secondary vacuum away from the plasma, was unable to deliver sufficiently focused beams over the whole steering range. The adoption of a front steering concept [5] has allowed a larger flexibility in the design of the beams, which in turn has led to an optimization of the distribution of the tasks between EL and UL [6].…”
Section: Introductionmentioning
confidence: 99%
“…Those RS system and installation of reflection mirrors have a benefit to separate the moving parts from the source region of the plasma neutrons, and it contributes to increase the reliability and to reduce the damage of the ECH system. Longpulse operation of normal electromagnetic mode has been verified in the LHD experiment [50][51][52]. The EBW heating with so-called the slow X-B and the O-X-B methods have been tested in overdens plasmas confined in the LHD [53,54].…”
Section: Echmentioning
confidence: 99%
“…Engineering requirements include a safely handled peak power load on the mirrors well below 10 MW/m 2 , millimetre wave stray power below 1%, and operation under ITER environmental conditions (magnetic field 6 T, ultra-high vacuum, vibration from cooling and shock from plasma disruptions). Various options of the RS concept have been explored and optimised in terms of effectiveness in NTM suppression [7]. Optimisation of the quasi-optical design has been carried out by [8].…”
Section: What Are the Requirementsmentioning
confidence: 99%